Types of Rationality in Discourses on Work in (Post)Transformation Poland - Kubala, Konrad (Qualitative Sociology Review, 2022)
Rationality is the key concept for understanding the reproduction of social life in the era of reflexive modernization. A fusion of lessons learned from the constructivist view of the world and analysis of the hermeneutic category of pre-understanding has become the basis of my belief that rationality is nowadays the basic modal concept, and the forms of its existence shape the order of social life. In my research practice, rationality has become a link between my interest in work and the theory of social order development. In this paper, I briefly present the relations between the notion of rationality and the theory of reflexive modernization. Then, I present my research path and the tools used in the analyses. The most important part is devoted to the effects of the conducted research. I classify and describe the types of rationality present in discourses on work in Poland. The discourses of politicians, experts, and the so-called “ordinary people” were analyzed.